KUALITAS PELAYANAN PERMOHONAN PENYEDIAAN PITA CUKAI (P3C) DI KANTOR PENGAWASAN DAN PELAYANAN BEA DAN CUKAI TIPE PRATAMA TEGAL - Kusuma, Adika; Widowati, Nina; Maesaroh, Maesaroh (Jurusan Administrasi Publik, Fakultas Ilmu Sosial dan Ilmu Politik, Universitas Diponegoro, 2013)
Claim players in the world of work there will be increasing service quality demands of stakeholders as key actors in the implementation of the development is expected to take an active role. This research problem is: How does the quality of services and the dimensions that result in less optimal in the service tax Tape Application Preparation (P3C) in Supervision and Service Office Pratama Type Tegal?The purpose of research is an important aspect of a study to describe and analyze quality of service as well as the dimensions of which result in the request for the provision of excise stamps (P3C) of tobacco products in the Office of Surveillance and Customs Services Primary Type Tegal less than optimal. In order to answer the problem and research objectives include the use of dimensional direct tangibels, relibility,responsiveness , competency, courtessy, credibility, security,acess , communication, Understanding the Customer.This study uses a qualitative descriptive technique using accidental sampling so that it can be explained the extent to which the provision of quality services tax stamp application (P3C) in the office of tobacco control and customs services tegal pratama type. There are two sources of primary and secondary data. This study using in-depth interviews, observation and dokumenasi related to service quality. The results showed that the quality of service can not be said to be good because there are still constraints that affect the quality of service such as the lack of access to the service counter, display a lack of readiness of personnel and lack of facilities and infrastructure to improve the quality of service in the Office of Surveillance and Customs and Excise Primary type of Tegal.